Felinos en los malecus: simbolización de la muerte como aliciente moral - Solano Fallas, Andrés (2017)
This paper deals with the philosophic implications present on the symbolization of death given by the maleku speeches on felines. First, this symbolization of death will be approach from two aspects: 1) the feline as a warning to third parties of the death of a relative, in order to which it will be contextualized the symbolic significance of the roar; and 2) the feline as a deserved punishment towards to whom is considered a reprobate. Second, it will be exposed that that symbolization has an impact on the moral acting, because the representation of the feline as a death giver works as a moral incentive for a “good” acting according to the general norms given by the gods.